Everyday aesthetics, space, and the sensory: fear of crime and affect in inner Sydney - Ellis, Justin R. (2021)
In this paper we explore pre-conscious aesthetic and sensorial aspects of affect in fear of crime. Drawing on data from focus groups undertaken in inner Sydney, Australia, we link the sensory and aesthetic preconditions of fear of crime to its affective, behavioural and cognitive elements. We argue that fear is grounded in the structural, personal and inter-subjective components of individual’s lives and their interaction with physical and social environments, which then influence how individuals cognitively understand their own risks and react behaviourally to these emotional responses. By bringing alive the importance of environmental cues and the cultural and structural positions of those who are likely to frequently worry about victimisation, we hope to provoke a minor reassessment of, and encourage more focus on, fear’s sensory and aesthetic origins